2019
DOI: 10.1002/ece3.4954
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and extinction dynamics among the plant species at tree bases in Paris (France)

Abstract: In cities, trees planted along streets could play an important ecological role for spontaneous plants growing at their bases. For example, these trees could represent corridors by potentially connecting large green spaces (e.g., parks, gardens), which allow species to move within the urban matrix. We considered sets of urban trees in 15 streets in Paris, France, as metapopulations for 15 plant species. Our objective was to determine the factors influencing the dynamics of colonization and extinction of populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 63 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…The increase in class‐level diversity over the decades broadens the prospects of applying SPOMS to a wider diversity of organisms. We found studies for species where metapopulation processes are hard to identify, such as long‐lived species (e.g., Juniperus spp., Pinus spp., Alados et al., 2009; Asimina obovata , Opuntia humifusa , Quintana‐Ascencio & Menges, 1996), species with dormant stages (e.g., Chenopodium album , Omar et al., 2019) or species living in apparently continuous habitats ( Litoria raniformis , Heard et al., 2012; Clinostomus elongatus , Poos & Jackson, 2012). The prevalent application of the less complex models, especially the IFM, throughout the decades together with the considerable presence of the species‐ or landscape‐specific models, suggests that the increase in taxonomic diversity is a combined result of the dissemination of simple models to other taxonomic groups and the evolution of more nuanced model structures that make more acceptable assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in class‐level diversity over the decades broadens the prospects of applying SPOMS to a wider diversity of organisms. We found studies for species where metapopulation processes are hard to identify, such as long‐lived species (e.g., Juniperus spp., Pinus spp., Alados et al., 2009; Asimina obovata , Opuntia humifusa , Quintana‐Ascencio & Menges, 1996), species with dormant stages (e.g., Chenopodium album , Omar et al., 2019) or species living in apparently continuous habitats ( Litoria raniformis , Heard et al., 2012; Clinostomus elongatus , Poos & Jackson, 2012). The prevalent application of the less complex models, especially the IFM, throughout the decades together with the considerable presence of the species‐ or landscape‐specific models, suggests that the increase in taxonomic diversity is a combined result of the dissemination of simple models to other taxonomic groups and the evolution of more nuanced model structures that make more acceptable assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are highly supportive of the rescue effect (Gotelli, 1991; Hanski, 1982), where immigration of individuals from surrounding populations decreases the extinction probability of a local population (Brown & Kodric‐Brown, 1977; Gotelli & Kelley, 1993; Schmidt & Beissinger, 2020). Although supported by theoretical models (Freckleton et al., 2005; Hanski, 1982), empirical evidence for the rescue effect decreasing regional and local extinction probabilities are somewhat divergent: while some early metapopulation studies have not found a strong correlation between the fraction of sites occupied and extinction probabilities (Gotelli & Kelley, 1993; Gotelli & Taylor, 1999b; Pfister, 1998), others have suggested that there is an effect (Dornier & Cheptou, 2012; Sutherland, Elston & Lambin, 2012; Bergerot et al., 2013; Vergara et al., 2016; Omar et al., 2019). For example, Taylor et al.…”
Section: Discussionmentioning
confidence: 99%
“…We then tested whether the estimated SBCE probability was affected by the nature of the closest green space (see Omar et al., 2019), the seed dispersal mechanism, the flowering months (extracted from the database of the collaborative network of French botanists ‘Tela botanica’, http://www.tela-botanica.org), the releasing height of the seeds and the seed weight (mean value obtained from the LEDA database, Kleyer et al., 2008). We used a mixed‐effect linear regression model with SBCE probability as response variable, in which we integrated a weighting vector to take into account the degree of confidence on the estimated SBCE probability.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the population of plants in urban tree bases is located inside an inhospitable matrix and has a high turnover, which makes metapopulation models particularly suited (Dornier et al., 2011). Studies using presence/absence data for various species present in urban tree bases considered as metapopulations were already carried out, but to our knowledge none accounted for seed bank potential presence in tree bases (Dornier et al., 2011; Omar et al., 2019). We also attempted to relate the SBCE probability to species traits and environmental characteristics.…”
Section: Introductionmentioning
confidence: 99%